STUDY ON PHYSICO-CHEMICAL CHARACTERISTICS OF VIRGIN COCONUT OIL (VCO) MADE BY COCONUT MILK CREAM FREEZING METHOD - Sapta Raharja dan Maya Dwiyuni (Department of Agroindustrial Technology, Bogor Agricultural University, 2008)
ABSTRACTMost commercial grade coconut oils are made from copr. Most of the copra is dried under the sun in the open air, where it is exposed to insects and mold. The standard end product made from copra is RBD (refined, bleached, and deodorized) coconut oil. Both high heat and chemicals are used in this method. Some alternative technology to make Virgin Coconut Oil (VCO) have been improved and investigated. These are, centrifugal force, fermentation, enzymes, etc. VCO was not made by using of heat and chemicals, it is just refining by washing with water, filtration, and centrifugation only. In this research, VCO was made by freezing and thawing the coconut milk to destruct the emulsion of coconut milk cream, then centrifugal force was used to separate the oil from coconut milk cream. The problem of this method was high moisture content, so it must be handled by adding of salt. Salt is hygroscopic so it can absorb some water. The characterizations were done for oil moisture content, oil yield, free fatty acid, acid value and peroxide value. The result showed that all of parameters meet the APCC standard.Keywords : Virgin Coconut Oil, VCO, milk cream freezing method.